After the boats disappear: forced migration, statelessness, and precarious belonging in Southeast Asian refugee narratives - Aisultanova Karlygash Abdukalykowna (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Forced migration in Southeast Asia increasingly reveals that maritime escape, rescue, or resettlement does not end refugee precarity when citizenship, documentation, and social recognition remain suspended. Objective: This study examines how Southeast Asian refugee narratives represent forced migration, statelessness, and precarious belonging after boats disappear from immediate public and humanitarian attention. Method: Using qualitative textual analysis, this study analyzes 19 publicly accessible documents consisting of refugee narratives, oral-history archives, humanitarian stories, public history materials, visual-documentary pages, and contextual institutional sources. Results: Findings show that maritime routes operate as narrative thresholds rather than closed episodes, because boats, camps, shelters, archives, and diasporic spaces form a continuous geography of unfinished displacement. Findings also indicate that statelessness is narrated through documentation absence, legal limbo, mobility restriction, humanitarian dependency, and intergenerational exclusion rather than through juridical language alone. Implication: Findings further demonstrate that testimony, family memory, digital archives, and visual representation function as fragile but meaningful practices through which refugees negotiate voice, history, and belonging. Novelty: This study contributes a narrative-spatial and legal-cultural framework that connects route, protection status, memory, and belonging, thereby repositioning Southeast Asian refugee narratives as critical sites for understanding post-arrival precarity.